Visibilité des aménités, invisibilisation des inondations. L’inondation dans l’écoquartier à La Riche (agglomération de Tours) - Mathilde Gralepois (Développement Durable et Territoires)
The article describes the use of nature in a French eco-district (La Riche, agglomeration of Tours) and the implications in terms of sustainable urban development in the face of climate change adaptation. The "staging of nature" is a constant, recurrent and understudied aspect of urban projects in flood-prone areas. The staging is produced by an arrangement of vegetal, architectural and communicational elements that enhance the proximity between the urban district and the nature. Even though the respect of the flood prevention rules determines urban development, the landscape, urban and architectural consequences – such as the upper-elevation, the restriction of the ground floor use or the important green surfaces – are ignored and retranslated into a sustainable public policy. The eco-district labelling process helps to negotiate and hide the risk of flooding, by highlighting the environmental qualities of the area.